Feelings of Parental Authenticity Moderate Concurrent Links Between Breastfeeding Experience and Symptoms of Postpartum Depression - Hammond, Mikayela; Brooker, Rebecca J.; Mistry-Patel, Sejal; Schlegel, Rebecca J.; Vess, Matthew; Wines, Maria; Havens, Jessica (Frontiers in Global Women's Health, 2021)
A negative breastfeeding experience is a contextual risk factor for the development of postpartum depressive symptoms among mothers. Many current interventions targeted at disrupting this association rely on the ability to make breastfeeding experiences positive. As a beginning step toward identifying alternative approaches, we investigated a potential psychological buffer of the negative relation between breastfeeding experience and symptoms of postpartum depression: feeling authentic in one's role as a parent. Authenticity appears to enhance well-being and buffer negative outcomes more generally, but has largely gone unaddressed in mothers, particularly during the critical peripartum period when depressive symptoms are at increased prevalence. We tested whether three facets of felt authenticity in the parent role (authentic living, acceptance of external influence, and self-alienation) moderated the association between satisfaction with breastfeeding experience and postpartum depressive symptoms in mothers (N = 92, 81% White, 85% non-Hispanic, college-educated, Mage = 30.49). We found that mothers who felt high in authentic living in the parent role showed fewer depressive symptoms when breastfeeding experiences were positive. In addition, we found that the association between negative breastfeeding experience and greater postpartum depression was mitigated when feelings of self-alienation in the parent role, or the sense that one is unaware of or disconnected from who “she really is” as a mother, were low. This work suggests that enhancing women's feelings of connectedness to “who they truly are” as a mother may be protective against some of the negative mental health effects linked to problems with breastfeeding.